Effect of Rhizophagus intraradices on growth and physiological performance of Finger Millet (Eleusine coracana L.) under drought stress - Tyagi, Jaagriti; Shrivastava, Neeraj; Sharma, AK; Varma, Ajit; Pudake, Ramesh (Plant Science Today, 2021)
Under abiotic stress conditions, arbuscular mycorrhizal (AM) fungi help plants by improving nutrient and water uptake. Finger millet (Eleusine coracana L.) is an arid crop having soils with poor water holding capacity. Therefore, it is difficult for the plants to obtain water and mineral nutrients from such soil to sustain life. To understand the role of mycorrhizal symbiosis in water and mineral up-take from the soil, we studied the role of Rhizophagus intraradices colonization and its beneficial role for drought stress tolerance in finger millet seedlings. Under severe drought stress condition, AM inoculation led to the significant increase in plant growth (7 %), phosphorus and chlorophyll content (29 %). Also, under drought stress the level of osmolytes such as proline and soluble sugars were found to be increased in AM inoculated seedlings. Under water stress, the lipid peroxidation in leaves of mycorrhized seedlings was reduced by 29 %. The flavonoid content of roots in AM colonized seedlings was found 16 % higher compared to the control, whereas the leaves were accumulated more phenol. Compared to the control, ascorbate level was found to be 25 % higher in leaf tissue of AM inoculated seedlings. Moreover, glutathione (GSH) level was also increased in mycorrhiza inoculated seedlings with a maximum increment of 182 % under severe stress. The results demonstrated that AM provided drought tolerance to the finger millet seedlings through a stronger root system, greater photosynthetic efficiency, a more efficient antioxidant system and improved osmoregulation.